A Review of samarium-containing bioactive glasses: biomedical applications - khosravi, Negin; Moradi, Aramis; Sharifianjazi , Fariborz; Tavamaishvili , Ketevan; Bakhtiari , Ameneh; Mohammadi , Ali (Journal of Composites and Compounds, 2025)
Samarium, a rare earth element, has gained significant attention in biomaterials due to its unique physicochemical properties and potential bioactivity. This review focuses on samarium-containing bioactive glasses, highlighting their composition and the role of samarium in enhancing bioactivity, biocompatibility, and antibacterial properties. The incorporation of samarium ions has been shown to influence the structural characteristics of bioactive glasses, promoting superior interaction with biological tissues and improved osteogenic activity. Incorporating samarium into bioactive glasses (BGs) enhances their bioactivity and mechanical strength. Various biomedical applications, including bone regeneration, drug delivery systems, and tissue engineering, are explored, showcasing the versatility and effectiveness of these materials in medical settings. A comprehensive analysis of recent literature reveals ongoing advancements in the properties and application of samarium-containing bioactive glasses, paving the way for future research and clinical applications in the field of regenerative medicine.